The burden of apathy for caregivers of patients with amyotrophic lateral sclerosis. Issue 7 (2nd October 2018) - Caga, Jashelle; Hsieh, Sharpley; Highton-Williamson, Elizabeth; Zoing, Margaret C.; Ramsey, Eleanor; Devenney, Emma; Ahmed, Rebekah M.; Hogden, Anne; Kiernan, Matthew C.
Abstract: Objectives: Apathy is the most common behavioral symptom of amyotrophic lateral sclerosis (ALS). Despite its known impact on caregiver wellbeing, apathy is typically considered a unitary construct making assessment and targeting treatment problematic. The aim of this study was to explore the relationship between caregiver burden and the behavioral, cognitive, and emotional symptoms of apathy in ALS. Methods: Fifty-one ALS patient-caregiver dyads from an ALS/frontotemporal dementia Clinic were assessed with the Apathy Evaluation Scale which measured the cognitive, behavioral, emotional, and nonspecific symptoms of apathy as well as the Zarit Burden Interview, a measure of perceived burden among caregivers of cognitively impaired older adults. The relationship between apathy and caregiver burden were analyzed using univariate and multivariate methods. Results: Apathy was identified in 18% of ALS patients. Greater behavioral ( p  = 0.011) and nonspecific ( p  = 0.010) symptoms of apathy exhibited by patients were reported by caregivers with higher levels of burden compared to caregivers with lower levels of burden. Of the cognitive, behavioral, emotional, and nonspecific symptoms of apathy, only the behavioral symptoms explained a significant amount of variance in caregiver burden ( p  = 0.031). Conclusions: Apathy, specifically the behavioral symptoms of apathy was associated with higher burden of care among ALS caregivers, highlighting the importance of multidimensional assessment of apathy and provision of behavior management support as part of ALS care.